PENGEMBANGAN POTENSI WISATA KAMPUNG TEMATIK KOKOLAKA DI KELURAHAN JATIREJO KECAMATAN GUNUNGPATI, KOTA SEMARANG - Salsabila, Safina (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
Thematic Village is one of Semarang City Government programst to alleviate poverty problems in Semarang City. Thematic Village is part of the